2021
DOI: 10.26803/ijlter.20.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Feedback Practice and Students’ Academic Achievement: A Systematic Literature Review

Abstract: Previous literature on teachers’ feedback practices has revealed that feedback has a strong effect on students’ academic performance. Nevertheless, feedback is a challenge for teachers to use in teaching and the learning environment due to time constraints and teachers’ inability to provide students with feedback they need for self-improvement. Furthermore, teachers are often unsure whether the feedback given will meet students’ academic needs as students have to work on improving themselves after receiving fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…Findings of the study conclude that overall learning motivation through constructive feedback has a significant impact on students' academic achievement in Chemistry subject.This findings are aligned with Fatima et al (2021) who argued the same that feedback is an integral part of any performance test. Students take constructive feedback positively in the evaluation and perform better as they know that learning happens with practice (Selvaraj et al, 2021). Finding of the study also suggest that the feedback that is delivered effectively has the power to increase effort, motivation, and engagement (Aslam, Khan, & Oad, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Findings of the study conclude that overall learning motivation through constructive feedback has a significant impact on students' academic achievement in Chemistry subject.This findings are aligned with Fatima et al (2021) who argued the same that feedback is an integral part of any performance test. Students take constructive feedback positively in the evaluation and perform better as they know that learning happens with practice (Selvaraj et al, 2021). Finding of the study also suggest that the feedback that is delivered effectively has the power to increase effort, motivation, and engagement (Aslam, Khan, & Oad, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…The feedback gave students a sense of appreciation which made students feel appreciated. As stated by Selvaraj et al, (2021), giving feedback is important because it may influence students' perceptions of the teachers' intentions and drive students to strive to be better. This dynamic between teacher and students would create a healthy learning environment which could strengthen the bond between teacher and students.…”
Section: Teacher's Rolementioning
confidence: 99%
“…Findings align with Fatima et al (2021), who argued the same point that feedback is an integral part of any performance test. Students take constructive feedback positively in the evaluation and perform better as they know that learning happens with practice (Selvaraj et al, 2021). Wisniewski et al (2020) and Hattie's (2009) meta-analysis also confirmed that feedback is essential due to its cognitive influences in any teaching-learning process.…”
Section: Conclusion and Discussionmentioning
confidence: 86%